2012
DOI: 10.1016/j.mambio.2011.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of small and medium-sized prey mammals in relation to their habitat preferences, age classes and locomotion types in the temperate Monte Desert, Argentina

Abstract: a b s t r a c tIn this study we examined predation by small felids upon small and medium-sized prey mammals in the central region of the Monte Desert. We analyzed the degree of vulnerability of prey mammals in relation to their habitat use patterns, modes of locomotion and age classes. Medium and small rodents were the predominant prey in the diet of small cats. The most consumed small mammal was Akodon molinae, which inhabits areas of dense cover, while species occurring in open habitats such as Eligmodontia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Vásquez (1996) and Taraborelli et al (2003) described the Chilean Oligoryzomys longicaudatus using bipedal locomotion when escaping and quadrupedal locomotion when moving at a slow speed or over short distances. Corley et al (1995) also described similar ability in Eligmodontia typus, which was consumed less than expected by foxes (Dusicyon culpaeus) in Chile; however, Bisceglia et al (2011) and Tabeni et al (2012) reported a positive selection for Eligmodontia typus by small felids in Argentina. In this latter case, E. typus is reported to use open (and risky) habitats.…”
Section: Selection and Vulnerabilitymentioning
confidence: 83%
See 4 more Smart Citations
“…Vásquez (1996) and Taraborelli et al (2003) described the Chilean Oligoryzomys longicaudatus using bipedal locomotion when escaping and quadrupedal locomotion when moving at a slow speed or over short distances. Corley et al (1995) also described similar ability in Eligmodontia typus, which was consumed less than expected by foxes (Dusicyon culpaeus) in Chile; however, Bisceglia et al (2011) and Tabeni et al (2012) reported a positive selection for Eligmodontia typus by small felids in Argentina. In this latter case, E. typus is reported to use open (and risky) habitats.…”
Section: Selection and Vulnerabilitymentioning
confidence: 83%
“…An efficient defence strategy not only involves a good hearing, visual or olfactory capability to detect the predator in advance but also a successful escape mechanism, such as bipedal hopping (Kotler 1984;Djawdan and Garland 1988;Hughes et al 1994;Taraborelli et al 2003;Bisceglia et al 2011;Tabeni et al 2012), which may interrupt the predation sequence (sensu Endler 1986) as the predator is approaching. The Brazilian Sigmodontines include several quadrupedal species of different sizes.…”
Section: Locomotionmentioning
confidence: 99%
See 3 more Smart Citations